SHE THINKS, HE SAYS: THE VOICE OF THE OTHER IN NOBEL LAUREATES’ GENDERED LITERATURE - Amamio, Regie Panadero (International Journal of Humanity Studies (IJHS), 2023)
The gendered language system is often used in literary works to present distinct character perspectives however, the issue of representation is accentuated when a writer presents a perspective of a different gender. Kawabata Yasunari and Gabriel Garcia Marquez who depicted female perspectives in their stories, have to face the issue of reliability of representation: theirs is argued asa patriarchal perception of a female’s perspective. Employing Spivak’s argument in Can the Subaltern Speak?, this paper positioned her statement as “through the perspective of the West (men), subaltern (women) become/s dependent on them (men) to speak for their condition rather than allowing them to speak for themselves.” This paper discussed the gendered language by examining the characters’ uncertain finitude utilizing Asher-Greve’s established gender markers to identify gender associations. Withthe stories of the two Nobel Laureates, this paper has established that through exploring the narrators’ usage of gendered language, both writers have inadvertently revealed their own male biases. The narrators of both writers turned out to be the voice of the other not because they have truthfully and successfully spoken for the marginalized; instead, they have become estranged voices of the subjects they are supposed to represent.Hence, the voices that cry for connection and understanding.